The concentration-independent effect of arbuscular mycorrhizal fungi on the tolerance of green foxtail to vanadium stress - Zhang, Shujuan; Dong, Yuexiao; Qi, Jingfan; Wang, Jinlong; Xi, Ze; Cao, Ziwei; Shah, Kinjal J.; You, Zhaoyang (Frontiers in Plant Science, 2025)
IntroductionArbuscular mycorrhizal fungi (AMF) show significant potential for improving plant tolerance to vanadium (V) stress. However, the pattern and physiological mechanisms behind this effect are not fully understood.MethodsTo investigate this, we used green foxtail (Setaria viridis) as a test plant and inoculated this plant with (+AMF) or without (-AMF) Rhizophagus irregularis. These +AMF and -AMF plants were grown in soils with low (150 mg kg-1), medium (500 mg kg-1), and high (1000 mg kg-1) V pollution levels.ResultsOur results showed root colonization of +AMF plants, whereas no such colonization was observed in -AMF plants. Compared to -AMF plants, +AMF plants showed a more organized arrangement of leaf cells, intact chloroplasts, fewer starch granules, and an intact nuclear membrane. AMF increased leaf chlorophyll a concentration by 49% under high V pollution and that of chlorophyll b by 18% under low V pollution and 36% at medium soil V levels. AMF reduced the concentration of malondialdehyde (MDA) by 36%-40% in leaves and increased the activities of superoxide dismutase (SOD) by 20%-84%, catalase (CAT) by 5%-13%, and peroxidase (POD) by 12%-16%. +AMF plants exhibited 13%-32% greater plant height, 17%-23% longer root length, 42%-78% higher shoot biomass, 61%-73% greater root biomass, 16% increased root-to-shoot ratio (at high V pollution), and 7%-13% elevated leaf phosphorus concentration than -AMF plants. Furthermore, +AMF shoots had 16%-30% lower V concentrations than -AMF plants while +AMF roots exhibited 52%-73% smaller V concentrations than the -AMF control.DiscussionThese results suggest that AMF increase plant tolerance to V stress by protecting leaf ultrastructure, increasing chlorophyll concentration, reducing oxidative damage as well as biomass-driven V dilution and these effects of AMF were independent of soil V concentrations.